+0  
 
0
257
1
avatar

8[7 - (6x - 6)] + 6x = 0.

Guest Aug 7, 2017
 #1
avatar+92463 
+1

8[7 - (6x - 6)] + 6x = 0      simplify inside the brackets first

 

8 [ 7 - 6x + 6 ]  + 6x  =  0

 

8 [ 13 - 6x ] + 6x  = 0

 

104 - 48x + 6x  = 0

 

104 - 42x  = 0    add 42x to both sides

 

104  =  42x   divide both sides by 42

 

104 / 42  = x  =  52 / 21

 

 

cool cool cool

CPhill  Aug 7, 2017

40 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.